PENGARUH HASIL PEMERIKSAAN BPK, KINERJA KEUANGAN PEMERINTAH DAERAH DAN UKURAN PEMERINTAH DAERAH TERHADAP NILAI INDEKS PERSEPSI KORUPSI PEMERINTAH DAERAH - Rifki Ahmad Pratama; Faisal Faisal (Diponegoro Journal of Accounting, 2016)
This study aimed to analyze the effect of the audit results by Audit Board of Indonesia (BPK), the financial performance of local governments and the size of local governments on the local governments corruption perception index. The variables tested in this research are audit opinion onthe financial statements of local government, the findings on the internal control system, the findings on compliance with laws and regulations, self-reliance ratio, growth ratio, the ratio of effectiveness and the size of local governments.This study uses secondary data derived from the results of the audit report by BPK on the financial statements of local governments in 2009 fiscal year and local governments corruption perception index derived from research reports by Transparency International Indonesia in 2010. The method uses in this study on selecting the samples are purposive sampling method. The data in this study tested using classic assumption test and correlation analysis. The hypothesis in this study tested using multiple linear regression analysis.The results showed that not all the audit results by BPK has a significant influence on the local goverments corruption perception index. Findings on compliance with the legislation is the only variable of the audit results by BPK with significant influence and negatively affect the local goverments corruption perception index. Based on the financial performance of local governments, the variables that have a significant influence on the local goverment corruption perception index only independence ratio and effectiveness ratio and which have a positive influence on the local goverment corruption perception index. The size of local governments have a significant negative effect on the local goverment corruption perception index.